Augmented Reality in the TPACK Framework: A Qualitative Analysis of Environmental Science Learning in Elementary Schools - Fitria Nurulaeni; Joko Suprapmanto (MASI Mandiri Edukasi, 2026)
This study examines the implementation of Augmented Reality (AR) in elementary environmental science learning through the Technological, Pedagogical, and Content Knowledge (TPACK) framework. Using qualitative data from interviews and classroom observations, the research identifies how teachers progressively integrate AR, moving from a technological orientation toward comprehensive pedagogical and conceptual alignment. Findings indicate that AR enhances students’ engagement, conceptual understanding, and ability to connect digital simulations with real environmental phenomena. Teachers demonstrate reflective adaptation by refining instructional strategies, guiding analytical discussions, and integrating ecological values into science instruction. The study further reveals a sustainable integration model characterized by three stages: technological familiarization, conceptual reinforcement, and reflective contextualization. Successful implementation depends not only on technological accessibility but also on teachers’ evaluative competence and institutional support. AR functions as an epistemic tool that facilitates experiential learning rather than merely providing visual enhancement. The TPACK framework is effective for conceptualizing the dynamic interplay among technology, pedagogy, and scientific content in environmental education. The research highlights the strategic importance of professional development and policy support to ensure the long-term sustainability of AR-based science learning innovations.